(untitled) (Nigerian Journal of Technology, 2022)
An iterative structural design process for the conventional, composite wing of a low speed, hybrid Unmanned Aerial Vehicle (UAV) is presented in this paper. The relevant design goals are light weight, strength and stiffness derived from the customer specifications, conceptual design and STANAG-4671 airworthiness standards. To achieve the design goals, a modified Taguchi model was applied in conducting iterative Finite Element Analysis of the loads and stresses on the wing model, using ABAQUS CAE. In this analysis, the pitch of the rib and thicknesses of the spar and skin were applied as control factors in three levels, leading to an L9 orthogonal array. Mass, maximum deflection and Tsai-Hill failure index of the wing structure were measured as responses. The result shows that varying the skin thickness had the most impact on the wing mass, failure index and maximum deflection. The design goal of wing mass- less than 2.5kg, deflection of 10% and Tsai-Hill failure index value- less than 1 were achieved after 9 iterations.